Nested Association Mapping (NAM) Populations: Present Status and Future Prospects in the Genomics Era. (2nd January 2021) - Gireesh, Channappa; Sundaram, Raman. M.; Anantha, Siddaiah M.; Pandey, Manish K.; Madhav, Maganti S.; Rathod, Santosha; Yathish, Kondajji R.; Senguttuvel, Ponnuvel; Kalyani, Barbadikar M.; Ranjith, Ellur; Venkata Subbarao, Lella; Kumar Mondal, Tapan; et al.
Abstract: Development of mapping population is a prerequisite for genetic dissection of genomic regions underlying complex traits. Nested Association Mapping (NAM) is an integrated multi-parent population approach that combines the advantages of linkage mapping and association mapping for high resolution and high-power mapping of complex traits. The NAM population is constituent of independent RIL populations derived from crossing several diverse donor parents with a common founder parent. The first NAM population was developed in maize and later on in several crops like barley, sorghum, wheat, rice, soybean, etc. This review provides an overview of NAM population development, its features, advantages over the other mapping populations, availability of high density genotyping platforms, key considerations for their development, applications and future prospects. We propose that the recent high-throughput analytical tools including high-end genotyping will accelerate utilization of NAM population for prediction of genomic estimated breeding value and genomic assisted selection in crop improvement program.